On a Class of Nonlinear Elliptic Problems Involving the $α(z)$-Biharmonic Operator with an $l(z)$-Hardy Term (Journal of Nonlinear Modeling and Analysis, 2025)
By applying the Mountain Pass Theorem, we establish the existence of a weak solution for a class of nonlinear elliptic problem involvingan $α(z)$-biharmonic operator and with an $l(z)$-hardy term in a bounded domain of $\mathbb{R}^N.$ Provided that certain additional assumptions are made regardingthe nonlinearities, the corresponding functional will satisfy the Palais-Smalecondition.